Identification of the effect and mechanism of Yiyi Fuzi Baijiang powder against colorectal cancer using network pharmacology and experimental validation - Xiang, Bin; Geng, Ruiman; Zhang, Zhengkun; Ji, Xuxu; Zou, Jiaqiong; Chen, Lihong; Liu, Ji (Frontiers in Pharmacology, 2022)
Background: Yiyi Fuzi Baijiang powder (YFBP) is a traditional Chinese medicine used to treat colorectal cancer, through its bioactivity and mechanisms of action have not yet been studied in depth. The study intended to identify the potential targets and signaling pathways affected by YFBP during treatment of colorectal cancer through pharmacological network analysis, and to further analyze its chemical compositions and molecular mechanisms of action. Methods: The Traditional Chinese Medicine Systems Pharmacology (TCMSP), Traditional Chinese Medicine Integrated Database (TCMID), Hit Predict(HIT) and Stitch Database (STITCH) were used to screen the bioactive components and promising targets of YFBP. Targets related to colorectal cancer were retrieved from the GENECARD and Gene Ontology databases. Cytoscape software was used to construct the “herb-active ingredient-target” network. The STRING database was used to construct and analyze protein-protein interactions (PPI). Afterwards, the R packages clusterProfiler and Cytoscapehub plug-in were used to perform Gene Ontology (GO) functional and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses of target genes. The results of the network pharmacological analysis were also experimentally validated. Results: In total, 33 active components and 128 target genes were screened. Among them, 46 target genes were considered potential therapeutic targets that crossed the CRC target genes. The network pharmacology analysis showed that the active components of YFBP correlated positively with CRC inflammatory target genes such as TLR4, TNF, and IL-6. The inflammation related signaling pathways affected by the active components included the TNF-α, interleukin-17, and toll-like receptor signaling pathways. The active ingredients of YFBP, such as luteolin, β-sitosterol, myristic acid, and vanillin, may exert anti-tumor effects by downregulating SMOX expression via anti-inflammatory signaling and regulation of the TLR4/NF-κB signaling pathway. Conclusion: In the present study, the potential active components, potential targets, and key biological pathways involved in YFBP treatment of CRC were determined, providing a theoretical foundation for further anti-tumor research.